Lower urinary tract symptoms among male medical students and its relationship with khat chewing habit: A cross‐sectional study. Issue 4 (31st May 2021) - Babakri, Mohammed M.; Al‐Sakkaf, Khaled; Basaleem, Huda
Abstract: Objective: To determine the prevalence of the khat chewing habit among male medical students and its relationship with urinary tract symptoms. Methods: This is a cross‐sectional study on male medical students at the University of Aden, Yemen, during the period 3 to 14 April 2016. The study tool was a self‐administered predesigned questionnaire containing selected personal background information, habits of chewing khat, and the standard Arabic version of the International Prostate Symptom Score (IPSS). Results: A total of 220 students completed the questionnaire; 46% of them reported using khat regularly. Fifty‐four (53.5%) students who chewed khat used it on a daily basis, and the vast majority of them (76%) spent more than 4 hours in a typical khat session. The main ± SD (median) IPSS of students who reported using khat was 10.48 ± 8.39 (10) compared with students who did not chew khat 2.89 ± 3.41 (2). The majority (90%) of the non‐khat chewing students had a mild degree of lower urinary tract symptoms (LUTS) and none of them reported a severe degree, while 39.6%, 46.5%, and 13.9% of the khat chewing students reported mild‐, moderate‐, and severe‐degree LUTS, respectively. There was a significant difference between khat chewing and non‐khat chewing students in all LUTS (domains of IPPS symptoms), except the nocturia symptom. Conclusion: The khat chewing habit is prevalent among male medical students, and it is strongly correlated with LUTS as measured by IPPS.